2018
DOI: 10.3892/etm.2018.5855
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different concentrations of uric acid on oxidative stress in steatosis hepatocytes

Abstract: Abstract. The development of nonalcoholic fatty liver disease (NAFLD) is caused by the steatosis of hepatocytes, which induces oxidative stress (OS). Thus, OS has an important role in the development of NAFLD. In the present study, the L-02 hepatocyte cell line was used to develop a steatosis cell model. The best model was determined using an MTT assay and the triglyceride levels. Model cells were treated with high concentrations of uric acid (UA; 0, 5, 10, 20 and 30 mg/dl) for 24, 48, 72 and 96 h. Indicators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…However, use of 20 mg/dL UA had no effect on this outcome. This finding is similar to that of our previous study (12) as well as other studies that have shown that normal serum UA concentration (5 mg/dL -------------------------------------------------- SIFT DESK in our study) could assist the body antioxidative system in preventing oxidative damage (11,14). Cells treated with UA demonstrated a decreased rate of apoptosis compared with model cells, in particular, cells treated with 5 mg/dL and 10 mg/dL of UA.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, use of 20 mg/dL UA had no effect on this outcome. This finding is similar to that of our previous study (12) as well as other studies that have shown that normal serum UA concentration (5 mg/dL -------------------------------------------------- SIFT DESK in our study) could assist the body antioxidative system in preventing oxidative damage (11,14). Cells treated with UA demonstrated a decreased rate of apoptosis compared with model cells, in particular, cells treated with 5 mg/dL and 10 mg/dL of UA.…”
Section: Discussionsupporting
confidence: 94%
“…The method used to develop a steatosis cell model was similar to that used in our previous study, described in detail elsewhere (12). Briefly, we prepared a 10-mM working solution by mixing 28.25 mg of oleic acid (OA) and 4 mg of NaOH in 10 ml of ultrapure water; this working solution was added to a standard medium to prepare sodium oleate medium with OA concentration of 0.3 mM.…”
Section: Steatosis Cell Model Development and Ua Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mainly decomposed from nucleic acids by enzymes or from other purine compounds metabolized by cells. UA is a reducing substance in the human body, participating in redox reactions and scavenging oxygen free radicals, thereby inhibiting oxidative stress [27,28]. Several studies have reported that serum UA is involved in the pathogenesis of OP by affecting oxidative stress and inflammatory cascades [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, when present at abnormally high levels it may become a risk factor for many metabolic syndromes and diseases (12)(13)(14)(15). SUA is a powerful scavenger of free radicals, which may contribute as an endogenous systemic antioxidant in protecting the bones from deterioration (16). Many experimental and epidemiological studies provided conflicting conclusions about the relation between SUA and bone health (17,18).…”
Section: Introductionmentioning
confidence: 99%